Palm Oil Soil Monitoring System for Smart Agriculture - Rawi, Roziyani; Iman Hasnan, Muhammad Shakhil; Abu Bakar Sajak, Aznida (International Journal of Integrated Engineering, 2020)
Palm oil is among the first commodity in Malaysia. The production of palm oil can be increased by implementing smart agriculture technology. To produce a good quality of palm oil, good soil quality is vital. Lack of soil information can make it hard for the farmer to maintain the nutritious of the oil palm tree. Thus, a real-time palm oil soil monitoring system has been developed for Palm Oil Soil Monitoring in a Smart Agriculture. The system measured the pH, moisture and tilt of palm oil soil. These parameters were essential to determine the palm oil soil status of alkalinity, tilt and moisture. These sensors are connected to Arduino microcontroller, which captures, processes and analyses the data. The captured data will be sent via the WiFi connectivity to the cloud database for the record. Based on the data analysis, the quality of the soil will be determined for further action by the farmer. The results showed that the system had successfully processed, transmitted, displayed and concluded the soil’s status. As a result, real-time reading will be displayed in the graphical graph using ThingSpeak.